2012
DOI: 10.1126/scitranslmed.3004485
|View full text |Cite
|
Sign up to set email alerts
|

Ser 1292 Autophosphorylation Is an Indicator of LRRK2 Kinase Activity and Contributes to the Cellular Effects of PD Mutations

Abstract: Mutations in the leucine-rich repeat kinase 2 (LRRK2) gene are the most common cause of familial Parkinson's disease (PD). Although biochemical studies have shown that certain PD mutations confer elevated kinase activity in vitro on LRRK2, there are no methods available to directly monitor LRRK2 kinase activity in vivo. We demonstrate that LRRK2 autophosphorylation on Ser(1292) occurs in vivo and is enhanced by several familial PD mutations including N1437H, R1441G/C, G2019S, and I2020T. Combining two PD mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
461
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(483 citation statements)
references
References 52 publications
(90 reference statements)
20
461
2
Order By: Relevance
“…In particular, we have shown that the LRRK2 mutants R1441H and S1444A, both of which prevent 14-3-3 binding to the ROC domain, had an ∼1.6 times enhanced LRRK2 kinase activity. This finding is in agreement with other studies in which enhanced kinase activity already was correlated with the PD-linked LRRK2 mutation R1441C (5,9). On the other hand, LRRK2 WT kinase activity is decreased in the presence of 14-3-3 and PKA in vitro, whereas LRRK2 S1444A (P-site) or R1441H (P-3 site) are unaffected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, we have shown that the LRRK2 mutants R1441H and S1444A, both of which prevent 14-3-3 binding to the ROC domain, had an ∼1.6 times enhanced LRRK2 kinase activity. This finding is in agreement with other studies in which enhanced kinase activity already was correlated with the PD-linked LRRK2 mutation R1441C (5,9). On the other hand, LRRK2 WT kinase activity is decreased in the presence of 14-3-3 and PKA in vitro, whereas LRRK2 S1444A (P-site) or R1441H (P-3 site) are unaffected.…”
Section: Discussionsupporting
confidence: 93%
“…Particularly for a single residue located within the ROC domain, three independent PDassociated mutations (R1441C, R1441G, and R1441H) have been found (4), whereas the kinase domain may harbor the most frequent pathogenic mutation, G2019S. Mutations at both these sites have been associated with enhanced kinase activity compared with wild type (5,6), suggesting that dysregulation of these enzymatic activities may contribute to PD pathogenesis.…”
mentioning
confidence: 99%
“…Direct evaluation of GTPase and kinase activity of N1437H LRRK2 has not yet been reported, although this variant does cause increased GTP binding [58]. When overexpressed in HEK293 cells, N1437H LRRK2 has an increased phosphorylation at Ser1292 [105] and diminished phosphorylation of Ser935 and, hence, 14-3-3 binding [92]. The measured effects are similar to other ROC-COR domain mutations, supporting pathogenicity.…”
Section: Lrrk2 Polymorphisms That May Affect Protein Functionmentioning
confidence: 81%
“…Although the exact biological function(s) of LRRK2 and its role in biochemical pathways are under investigation, several potential substrates have been identified, including LRRK2, Akt1, ezrin/radxin/moesin (ERM) proteins, β-tubulin, eukaryotic initiation factor 4E-binding protein 1, and mitogenactivated kinase 3, 4, 6, and 7 [13,[22][23][24][25][26][27][28][29][30][31][32][33][34]. The functional implications of the majority of these potential substrates with respect to LRRK2 patho-and physiological actions remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The functional implications of the majority of these potential substrates with respect to LRRK2 patho-and physiological actions remain uncertain. However, the work of Sheng et al [34] has directly implicated LRRK2 Ser1292 in pathogenic effects in cultured cells.…”
Section: Introductionmentioning
confidence: 99%